Perceptions about the AgriSETA skills training program by three selected farmer cooperatives (or farmer cooperative societies) in the North West and Mpumalanga provinces, South Africa - Stevens, Joe (University of Pretoria, 2023)
Dissertation (MSc (Agricultural Extension))--University of Pretoria, 2023.